Generation impact : international perspectives on impact accounting - Richards, Adam; Nicholls, Jeremy (Emerald Publishing Limited, 2021)
Mistrust in big business and major politicians, coupled with recent scandals in international development, grew from a blatant lack of accountability between decision-makers and recipients. Remedies seem to lie within the UN Sustainable Development Goals, the rise of social entrepreneurship, and the demand for responsible practices, all key drivers for social, rather than merely ficial, returns on investments. Yet accounting for such returns remains scattershot and unevenly implemented. With contributions from world-leading scholars and practitioners, Generation Impact brings together lessons from both developed and developing economies, shares current best practice and suggests future trends in impact accounting. The book analyses social and environmental capital protocols, the international convergence in impact investing, organisational management and capacity-building and best practice in assurance and training, and offers reflections on policy directions. Through its case-studies it provides insights into a growing global community of practitioners, academics, impact investors, policy-makers and organisations of all kinds working to cement the central importance of accounting for social value. For its unique blend of scholarly research and boots-on-the-ground insights, Generation Impact is a must-read for development scholars and students interested in social and environmental accounting, practitioners, senior managers, and executives concerned with organisational practice and its real impact on wider social and economic development.